Les savants et la sorcière - Eléonore Devevey; Jacob Lachat (Contextes)
Based on the analysis of two critical texts devoted to Jules Michelet's La Sorcière (1862), Roland Barthes’ “La Sorcière” (1959) and Jeanne Favret-Saada’s “Sorcières et Lumières” (1971), this article intends to investigate the logics behind the reception of La Sorcière during the 1950s-1970s. This book was indeed a focus of critical analysis for researchers in the human and social sciences, at the time when these fields were getting more institutional. The two articles we discuss are typical of a period during which the notion of myth, under the impetus of Lévi-Strauss’ work, permeated most disciplines and debates on the epistemology of the human sciences. They are also evidence of questions (and doubts) specific to a merging of knowledge, which affected the relationship between anthropology and literary studies, and, more broadly, the relationship between science and belief. Finally, they question the foundations and the blind spots of knowledge modalities in the human and social sciences, and especially the subjective commitment of the scholar in the work of knowledge.